Highly coloured and electrophoretically active polymer microparticles via staggered dispersion polymerisation in supercritical carbon dioxide and dodecane. Issue 39 (23rd September 2019) - McAllister, Thomas D.; Bennett, Thomas M.; Petrillo, Chiara; Topping, Claire; Farrand, Louise D.; Smith, Nathan; Howdle, Steven M.
Abstract : Well-defined, strongly coloured and electrophoretically active poly(methyl methacrylate) microparticles in one-pot, via dispersion polymerisation in supercritical carbon dioxide and dodecane. Abstract : Devices featuring electrophoretic displays (EPD) have become extremely popular in recent years because of their low power consumption, high readability and thin display designs, but a product with a full colour gamut comparable with liquid crystal displays (LCDs) has not yet been commercialised. In this article, we demonstrate that staggering the addition of methyl methacrylate (MMA) monomer and low quantities of a coloured dye crosslinker is an effective route to producing well-defined and covalently-linked, strongly coloured PMMA microparticles in one-pot, via dispersion polymerisation in supercritical carbon dioxide (scCO2 ). This novel methodology is synthetically simple, readily scalable and has the added cachet of being cost effective because the functional molecules can be confined on the microparticle surface such that even at low concentrations, the resulting materials are brightly coloured. We then demonstrate the applicability of this approach to another functional comonomer/crosslinker system in 2-dimethylaminoethyl methacrylate (DMAEMA)/ethyleneglycol dimethacrylate (EGDMA), in this case allowing hierarchically structured 'pomegranate-like' microparticles with polarisable charge to be produced over a range of DMAEMA loadings as high as 44 wt%. Finally, the performance of these materials in out-of-plane EPD test cells is compared against analogues synthesised in dodecane. These tests revealed that the coloured microparticles fabricated in scCO2 performed as well as or better than their dodecane synthesised counterparts, consistently producing the cleanest white state and achieving effective colour switching over ten cycles.